Are Korean industry-sorted portfolios mean reverting? - Seongman Moon (East Asian economic review, 2016)
This paper tests the weak-form efficient market hypothesis for Korean industry-sorted portfolios. Based on a panel variance ratio approach, we find significant mean reversion of stock returns over long horizons in the pre Asian currency crisis period but little evidence in the post-crisis period. Our empirical findings are consistent with the fact that Korea accelerated its integration with international financial market by implementing extensive capital liberalization since the crisis.
10.11644/KIEP.EAER.2016.20.2.308; 10.11644/KIEP.EAER.2016.20.2.308; 2862898-6; 2508-1667; East Asian economic review; 863610854